2021
DOI: 10.4490/algae.2021.36.6.5
|View full text |Cite
|
Sign up to set email alerts
|

A chemosystematic investigation of selected <italic>Stichococcus</italic>-like organisms (Trebouxiophyta)

Abstract: The taxonomy of green microalgae relies traditionally on morphological traits but has been rapidly changing since the advent of molecular methods. Stichococcus Nägeli is a cosmopolitan terrestrial algal genus of the class Trebouxiophyceae that has recently been split into seven lineages, which, along with Pseudostichococcus, comprise the Stichococcuslike group; there is a need to further characterize these genera, since they are morphologically enigmatic. Here we used organic osmolytes as chemotaxonomic marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Proline, together with sorbitol, is among the key compatible solutes associated with protection from damage induced by various stress factors interfering with osmoregulation, such as dehydration [ 56 , 57 ]. The higher sorbitol and proline contents in D. epiphytica were confirmed using an HPLC assay and a spectrophotometric assay, respectively ( Table S2 ), in agreement with previous work on the same strain (SAG 11.88) and D. chodatii , showing that sorbitol is present at high concentrations [ 16 , 17 , 18 ]. Several sugars and sugar alcohols, including sorbitol, have been suggested to play a role in desiccation tolerance [ 30 , 32 ], but they also play a role in the lichen symbiosis [ 31 , 32 , 58 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Proline, together with sorbitol, is among the key compatible solutes associated with protection from damage induced by various stress factors interfering with osmoregulation, such as dehydration [ 56 , 57 ]. The higher sorbitol and proline contents in D. epiphytica were confirmed using an HPLC assay and a spectrophotometric assay, respectively ( Table S2 ), in agreement with previous work on the same strain (SAG 11.88) and D. chodatii , showing that sorbitol is present at high concentrations [ 16 , 17 , 18 ]. Several sugars and sugar alcohols, including sorbitol, have been suggested to play a role in desiccation tolerance [ 30 , 32 ], but they also play a role in the lichen symbiosis [ 31 , 32 , 58 ].…”
Section: Discussionsupporting
confidence: 90%
“…Trebouxiophyceae are widespread globally, and occur in many aquatic and terrestrial ecosystems [ 9 , 10 , 11 ] with different lifestyles [ 2 , 12 ] either free-living or as lichen photobionts [ 13 , 14 , 15 ]. Ecophysiological traits of D. epiphtica and D. chodatii were recently reported [ 16 , 17 , 18 ]. In D. epiphtica , sorbitol and sucrose contents were used as chemotaxonomic markers [ 16 ], and the potential of Diplopshaera spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the genus Pseudostichococcus as a whole is more halotolerant than others within the Stichococcus-like clade. The hitherto monotypic genus Pseudostichococcus has been revised to also include the strains Pseudostichococcus sequoieti LB 1820 and Pseudostichococcus undulatus CALU-1142 used in this study, and that the latter strains belong to a second, possibly not halotolerant clade, within Pseudostichococcus [40]. Further studies are needed to delineate the ecological traits of Pseudostichococcus from those of the other Stichococcus-like strains.…”
Section: Growth In Response To Saline Stressmentioning
confidence: 99%
“…As with the other Stichococcus-like organisms, Pseudostichococcus are present in a variety of habitats, such as such as tree bark, surfaces of buildings and outdoor structures, diverse soils and are also components of biocrusts. A previous study indicated that Pseudostichococcus may be more halotolerant than previously assumed, as those strains retained vitality despite cultivation at very high salinities [39].…”
Section: Introductionmentioning
confidence: 86%